PENGUATAN SIKAP NASIONALISME MELALUI PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN PADA SEKOLAH INTERNASIONAL (Studi pada Secondary School di Singapore Piaget Academy Solo Raya) - Eka Sari; Yusuf Ali (Program Studi Pendidikan Pancasila dan Kewarganegaraan FKIP Universitas Sebelas Maret, 2018)
The results of research are as follows: (1) the implementation of the reinforcement of nationalism attitudes through Civic Education learning on Secondary School at Singapore Piaget Academy of Solo Raya has run well through the phases of planning, implementation, and assesment as indicated in the learning process that the indicators of nationalism attitudes are always implanted to the learners’ minds, which includes: (a) Indonesian language, (b) knowledge of nationality, (c) domestic product consumption, (d) professionalism, (e) upholding unity and integrity, (g) giving priority to the public interest, (h) building of sense of brotherhood, and (i) participation; and (2) the constraints include substantial and technical ones. The former consist of the students’ low interest and the teacher’s low pedagogical competency. Meanwhile, the latter include the less time for the learning process.Keywords : LNationalism, Civicl Education, Internationall School